2019
DOI: 10.1080/0267257x.2019.1680569
|View full text |Cite
|
Sign up to set email alerts
|

The rise of smart consumers: role of smart servicescape and smart consumer experience co-creation

Abstract: Rapid technological advancements have led to the emergence of smart services and smart consumers. This study focuses on smart consumers who voluntarily engage in value creation activities, in order to conceptualise smart experience co-creation (SEC) and the smart servicescape. Drawing on the Stimulus-Organism-Response (SOR) framework, a model is proposed and tested around the impacts of smart servicescape dimensions (aesthetics, superior functionality, social presence, perceived interactivity and perceived per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 172 publications
(180 reference statements)
1
78
0
Order By: Relevance
“…The findings show that servicescape from two points of view: Physical and social, are significant predictors on co-created value [113]. Thus, the findings of this research imply that the assumption of value co-creation concept is that customers will play an active role in collaborating with the firms for the creation of value together through the various stages of the value chain from service production to consumption [114]. Therefore, if the physical environment is supportive for tourists to take part in value creation and interact with employees and other tourists, created value is obvious to be developed.…”
Section: Discussionmentioning
confidence: 63%
“…The findings show that servicescape from two points of view: Physical and social, are significant predictors on co-created value [113]. Thus, the findings of this research imply that the assumption of value co-creation concept is that customers will play an active role in collaborating with the firms for the creation of value together through the various stages of the value chain from service production to consumption [114]. Therefore, if the physical environment is supportive for tourists to take part in value creation and interact with employees and other tourists, created value is obvious to be developed.…”
Section: Discussionmentioning
confidence: 63%
“…In sum, this manuscript lays the foundation for a better understanding of customers' interaction choices (Barwitz and Maas 2018) in the smart BaM servicescape (Sanjit K. Roy et al 2019) and offers ample opportunities for further research.…”
Section: Resultsmentioning
confidence: 92%
“…While prior research finds that the evaluation of service offerings is significantly more important for customers in ecommerce settings, it also suggests that there are no differences in the service orientations of BaM and e-commerce customers (Schramm-Klein et al 2007). Furthermore, in a smart servicescape (Sanjit K. Roy et al 2019), experience with technology has a mediating impact on customers' behavioral intentions toward such technologies and their loyalty toward the retailer (Roy et al 2017). The variables that are known from channel choice and technology acceptance studies in an e-commerce context are also shown to affect the purchase intention in omni-channel environments (Juaneda-Ayensa et al 2016; Kazancoglu and Aydin 2018;Susanto et al 2018).…”
Section: Perception Of Mediummentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies focus on traits of the virtual community that encourage these behaviors. These prior studies stress that aesthetic characteristics of the virtual community-for example, its capability to encourage interaction among participants and improve their feeling of social presence; or superior functional, utilitarian, or physical performance-give rise to greater perceived utility of the virtual community and thus foster value co-creation [35,36].…”
Section: Factors Impacting Co-creation Behaviorsmentioning
confidence: 99%